ZAHIRIDDIN MUHAMMAD BABUR: A PROMINENT STATESMAN AND GREAT COMMANDER OF THE TEMURID DYNASTY (Modern education and development, 2025)
One of the unique figures who left an indelible mark on world history, Zahiriddin Muhammad Babur is known and famous throughout the world as a great poet, encyclopedist, statesman and skilled commander. His incomparable scientific and creative heritage occupies a special place not only in the formation of our national culture and the literary and aesthetic thinking of our people, but also in the history of world literature, science and statehood. This article is devoted to the study of the historical legacy of Zahiriddin Muhammad Babur, in particular, to the analysis of his role as the successor of the Timurid dynasty. Babur, through his military and political activities, managed to continue the political and cultural legacy of the Timurid dynasty in Central Asia and India. The political system, military campaigns, state administration and cultural values of the Timurid era were of great importance to Babur. The article analyzes how Babur continued the main political and cultural values of the Timurid state in his activities. It also shows that the Timurid legacy reached a new level through the empire founded by Babur in India. Babur continued not only the political system of the Timurids, but also their legacy in the fields of science, art and architecture, creating a new cultural environment in India.